2011
DOI: 10.1007/s10546-011-9667-4
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Direction Effects on Urban-Type Flows

Abstract: Practically all extant work on flows over obstacle arrays, whether laboratory experiments or numerical modelling, is for cases where the oncoming wind is normal to salient faces of the obstacles. In the field, however, this is rarely the case. Here, simulations of flows at various directions over arrays of cubes representing typical urban canopy regions are presented and discussed. The computations are of both direct numerical simulation and large-eddy simulation type. Attention is concentrated on the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 31 publications
(58 reference statements)
0
33
0
Order By: Relevance
“…Staggered and non-uniformly oriented groups of roughness elements generate a larger drag force than regular arrays, causing a more pronounced peak in z 0 , as well as larger values of z d (Macdonald 2000;Cheng et al 2007;Hagishima et al 2009;Zaki et al 2011;Claus et al 2012). Roughness-element height variability also influences flow and turbulent characteristics, as the taller roughness elements generate a disproportionate amount of drag (Xie et al 2008;Mohammad et al 2015b).…”
Section: Relations Between Aerodynamic Parameters and Roughness-elemementioning
confidence: 99%
“…Staggered and non-uniformly oriented groups of roughness elements generate a larger drag force than regular arrays, causing a more pronounced peak in z 0 , as well as larger values of z d (Macdonald 2000;Cheng et al 2007;Hagishima et al 2009;Zaki et al 2011;Claus et al 2012). Roughness-element height variability also influences flow and turbulent characteristics, as the taller roughness elements generate a disproportionate amount of drag (Xie et al 2008;Mohammad et al 2015b).…”
Section: Relations Between Aerodynamic Parameters and Roughness-elemementioning
confidence: 99%
“…) along alternate rows in the figure. At right plan view of DIPLOS array of h × 2h × h cuboids (Castro et al 2016) directions and in a half-channel with H = 4h, have also been reported (Claus et al 2012); grid sizes were typically Δ = h/25 over the canopy height. A 'random height' extension of the case of the staggered cube array with λ p = 0.25 was that initially studied experimentally by Cheng and Castro (2002) and subsequently computationally by Xie et al (2008) .…”
Section: The Flows Consideredmentioning
confidence: 85%
“…Note that the lateral force normal to the forcing direction must inevitably be zero in 561 a numerical computation, as explained by Claus et al (2012). We therefore conclude 562 that small numerical inaccuracies are sufficient to produce the asymmetry in W and,…”
mentioning
confidence: 78%